Association between periodontitis and bipolar disorder: A nationwide cohort study. Issue 31 (31st July 2020) - Chang, Kuang-Hsi; Hsu, Yi-Chao; Chiu, Ing-Ming; Chen, Lih-Chyang; Hsu, Chih-Chao; Lee, Chang-Yin; Fan, Hueng-Chuen; Chen, Hsuan-Ju; Chou, Ruey-Hwang
Abstract : Abstract: Whether periodontitis is a risk factor for developing bipolar disorders (BD) has not been investigated. We aimed to determine whether periodontitis is associated with the subsequent development of BD and examine the risk factors for BD among patients with periodontitis. Using ambulatory and inpatient claims data from the National Health Insurance Research Database (NHIRD), we identified 12, 337 patients who were aged at least 20 years and newly diagnosed with periodontitis between 2000 and 2004. The date of the first claim with a periodontitis diagnosis was set as the index date. For each patient with periodontitis, 4 subjects without a history of periodontitis were randomly selected from the NHIRD and frequency-matched with the patients with periodontitis according to sex, age (in 5-year bands), and index year. The periodontitis group had a mean age of 44.0 ± 13.7 years and slight predominance of men (51.3%). Compared with the subjects without periodontitis, the patients with periodontitis had higher prevalence of diabetes mellitus, hyperlipidemia, hypertension, ischemic heart disease, stroke, head injury, major depressive disorder, chronic obstructive pulmonary disease (COPD), and asthma ( P  < .001). The incidence rate of BD was higher in the periodontitis group than in the non-periodontitis group (2.74 vs 1.46 per 1000 person-year), with an adjusted hazard ratio of 1.82 (95% confidence interval = 1.59–2.08) after adjustment for sex, age, and comorbidities. The patients with periodontitis exhibited a significantly higher risk of developing BD. Keep the better oral hygiene to reduce periodontitis might be a preventive strategy for BD.